THE EFFECT OF FINANCIAL PERFORMANCE OF COMPANIES ON SHARE RETURN IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE YEAR 2014 -2016 - Paryanto Paryanto; N. Dicky Sumarsono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2018)
This study aims to determine the effect of parsiil and simultaneous price book value, price earnings ratio, earnings per share and dividend pay out ratio to stock returns on manufacturing companies listed in Indonesia Stock Exchange 2014-2016. The technique of determining the sample in this research is by using purposive sampling. There are several criteria that must be met by companies listed in Indonesia Stock Exchange to be a sample in this research. This research method uses multiple regression analysis which is used to know the influence of independent variable to dependent variable together and partially. The test t is used to test the influence of each price book value variable, price earning ratio, earnings per share and dividend pay out ratio) to stock return variables. Statistical test F aims to examine the influence of price book value variable, price earning ratio, earnings per share and dividend pay out ratio) together to stock return variables. Test R2 (Coefficient of determination) is done to find out how much influence the variable of price book value, price earning ratio, earnings per share and dividend pay out ratio to stock return variable. From result of t test known that price book value, earnings per share and dividend pay out ratio partially significant effect to stock return. Variable Price Earning Ratio partially no significant effect on stock return variables. From result of F test known that Price Book Value, Price Earning Ratio, Earning Per Share and Dividend Pay Out Ratio simultaneously have an effect on signifikan to variable Return of Shares In Manufacturing Company Listed In Indonesia Stock Exchange Year 2014 -2016. Keywords : PBV, PER, EPS, DPR, Stock Return